Allosteric modulation of monomeric proteins - ASCENZI, Paolo; BOCEDI, ALESSIO; BOLLI, ALESSANDRO; POLTICELLI, Fabio; FASANO MAURO; NOTARI STEFANIA (2005)
Multimeric proteins (e.g., hemoglobin) are considered to be the prototypes of allosteric enzymes, whereas monomeric proteins (e.g., myoglobin) usually are assumed to be non-allosteric. However, the modulation of the functional properties of monomeric proteins by heterotropic allosteric effectors casts doubts on this assumption. Here, the allosteric properties of sperm whale myoglobin, human serum albumin, and human thrombin, generally considered as molecular models of monomeric proteins, are summarized.